Investigating dissolved organic matter cycling in High Arctic ponds and soils - Thiel, Gillian (2018)
As the most bioavailable fraction of organic matter, dissolved organic matter (DOM) plays an important role in the carbon (C) cycle. Heterotrophic microorganisms degrade DOM and release it to the atmosphere as carbon dioxide (CO2) under oxygenated conditions. However, some DOM may be more readily bioavailable (i.e., labile) to microorganisms than other DOM. In the past, lability has been defined mainly by DOM molecular structure, but more recent research suggests that environmental conditions such as nutrient availability may also control lability. DOM lability has been investigated extensively in Arctic lake and large river systems, however relatively little research has investigated the lability of DOM in systems with more fine scale spatial heterogeneity in environmental conditions, such as ponds and soils. Chapter 2 presents a study of environmental conditions and molecular structure as controls on the lability of DOM in six High Arctic ponds at the Cape Bounty Arctic Watershed Observatory (CBAWO) through short-term incubation experiments, optical properties, and chemical analyses. Chapter 3 explores the role of soil DOM in soil C respiration at the beginning, middle, and end of the growing season across the five major land cover classes at the CBAWO: active layer detachment scar, mesic tundra, unvegetated polar desert, vegetated polar desert, and wet sedge. Soil CO2 emissions were measured over short-term soil incubation experiments and compared with the optical and chemical characteristics of soil water-extractable organic matter (WEOM) before and after incubation. Results indicate that pond DOM lability depends on both environmental conditions and DOM molecular structure, and is therefore dependent on geomorphic characteristics which determine subsurface water and nutrient delivery. The soils study confirms statistically significant variability in CO2 emissions between vegetation types. The study also indicates that WEOM is highly labile and makes an important contribution to total C respiration. Overall ...